Nanocrystalline formation in amorphous Fe79B16Si5 and Fe78B13Si9 ribbons - S. Thongmee (2018)
Nanocrystalline formation in the amorphous ribbons, Fe79B16Si5 and Fe78B13Si9, resulting from annealing the ribbons at temperatures below their crystalline temperature is followed by Mossbauer spectroscopy. It is seen that in the B-rich Fe78B16Si5 ribbons, the crystallization is a two stage process: amorphous → α-Fe(Si) nanocrystalline formation → (α-Fe, Fe2B) nanocrystalline formation while the crystallization in the B-poor Fe78B13Si9 ribbons is a three stage process: amorphous → Fe3B nanocrystalline formation → α-Fe(Si) nanocrystalline formation → (α-Fe, Fe2B) nanocrystalline formation. These direct observation confirms the inferred formation of nanocrystallites obtained from magnetization measurements of similar type Fe-Si-B amorphous alloys. Our study also indicated that the α-Fe(Si) nanocrystallites survives at the higher temperatures. © World Scientific Publishing Company.